Anatomy and baseline histology of the hoof capsule, corium, and digital cushion in free-ranging southern giraffe (Giraffa giraffa) - Liza Dadone; Steve Foxworth; Jacqueline Goedhals; Sushan Han; Priya Bapodra-Villaverde; Seng Wai Yap; Thato Radile; Francois Deacon (PLoS ONE, 2025)
The front feet of six adult free-ranging southern giraffe (Giraffa giraffa ) were opportunistically examined to characterize normal hoof anatomy, focusing on the corium (dermis), which provides vascular supply, metabolic support, and structural templates for the overlying epidermis that generates the keratinized hoof capsule. Gross dissection and histology identified two types of corium on the surface of the distal phalanx (Pd): laminae and papillae. On the parietal surface of Pd, laminae covered approximately its distal two-thirds and, as in other ruminants, secondary laminae were absent. Papillae varied regionally, with the longest and thickest located at the distal margins of Pd. On the solar surface, horn tubules were oriented obliquely in a palmar-proximal to dorso-distal direction. Within the hoof, the digital cushion consisted of a proximal adipose-rich region and a distal fibroelastic region. Histological findings were unremarkable and supported gross observations of normal anatomy. Examination of Pd and the navicular (distal sesamoid) regions revealed no evidence of pedal osteitis, navicular pathology, laminitis, or other lesions. These data provide a reference for normal giraffe foot anatomy and histology. Improved understanding of the corium and associated structures that support hoof capsule growth may inform preventative hoof care, reduce risk of overgrowth, and assist in managing lameness in both zoo-housed and free-ranging giraffe.